Early nurse attrition in New Zealand and associated policy implications. (28th November 2017) - Walker, L.; Clendon, J.
Abstract : Aim: To examine the factors contributing to nurses choosing to exit the nursing profession before retirement age. Background: Population growth, ageing and growing demand for health services mean increased demand for nurses. Better retention could help meet this demand, yet little work has been done in New Zealand to understand early attrition. Methods: An online survey of registered and enrolled nurses and nurse practitioners who had left nursing was used. This study reports analysis of responses from 285 ex‐nurses aged under 55. Findings: The primary reasons nurses left the profession were as follows: workplace concerns; personal challenges; career factors; family reasons; lack of confidence; leaving for overseas; unwillingness to complete educational requirements; poor work–life balance; and inability to find suitable nursing work. Most nurses discussed their intentions to leave with a family member or manager and most reported gaining transferrable skills through nursing. Conclusions: Nurses leave for many reasons. Implementing positive practice environments and individualized approaches to retaining staff may help reduce this attrition. Generational changes in the nature of work and careers mean that nurses may continue to leave the profession sooner than anticipated by policymakers. Implications for policy: If the nursing workforce is to be able to meet projected need, education, recruitment and retention policies must urgently address issues leading to early attrition. In particular, policies improving the wider environmental context of nursing practice and ensuring that working environments are safe and nurses are well supported must be developed and implemented. Equally, national nursing workforce planning must take into account that nursing is no longer viewed as a career for life.